Sartre, Minkowski and Depression (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
This paper explores the relationship between the ideas of Minkowski, a psychiatrist working at the beginning of the 19th century, Sartre, a key existential philosopher, and depression. Minkowski's exploration of the time dimension and Sartre's writings on choice, responsibility and self-construction are considered in relation to depression and psychotherapy.
Keywords: Depression; Sartre; Minkowski; existential; time; phenomenology; personal impetus